Genetics of extra-early-maturing yellow and orange quality protein maize inbreds and derived hybrids under low soil nitrogen and Striga infestation - Badu-Apraku, B.; Abu, Pearl; Ifie, Beatrice (Crop Science Society of America, 2020)
The development and commercialization of extra-early quality protein maize (QPM)-provitamin A (PVA) hybrids, tolerant of low soil nitrogen (LN) and Striga resistant are essential for addressing the food insecurity and undernourishment challenges currently faced by sub-Saharan Africa (SSA). This study was designed to (i) determine the genetic effects regulating grain yield (GY) and important secondary traits of extra-early yellow and orange QPM-PVA inbred lines under LN, Striga-infested and high-nitrogen (HN) conditions, (ii) investigate whether maternal genes influenced the inheritance of GY and other secondary traits,(iii) assess the GY and stability of the hybrids across the three management conditions, and (iv) examine the relationship between single nucleotide polymorphism (SNP) marker-based genetic distances and GY. Twenty-four inbred lines were used to produce ninety-six single cross hybrids employing the North Carolina Design II. The performance of the hybrids plus four checks was assessed across LN, Striga-infested and HN management conditions in Ghana and Nigeria in 2018. Additive genetic variances were preponderant over non-additive genetic variances for GY and most secondary traits in each and across environments. TZEEQI 358 exhibited significant and positive male and female GCA effects for GY under LN, Striga-infestation, HN and across management conditions indicating that favourable alleles for GY could be donated by TZEEQI 358. Maternal effects regulated the inheritance of plant height under the Striga-infested conditions. Genetic distances were associated with GY under LN, Striga-infestation and HN conditions. TZEEIORQ 58 × TZEEQI 397 demonstrated high GY and stability of performance; therefore, it should be further tested under multiple environments for commercialization.
Crop Science, Volume 61, Issue 2
Keywords: Pangirayi Tongoona; Priscilla F. Ribeiro; Ebenezer Obeng-Bio; Samuel Kwame Offei; Agriculture; University of Ghana